2004
DOI: 10.1016/s0378-1097(03)00862-0
|View full text |Cite
|
Sign up to set email alerts
|

PicU, a second serine protease autotransporter of uropathogenic Escherichia coli

Abstract: Escherichia coli is the major aetiological agent of urinary tract infections (UTI). Like diarrhoeagenic strains of E. coli, uropathogenic isolates possess virulence determinants that distinguish them from commensal strains and allow them to produce the clinical manifestations associated with UTI. Several autotransporter proteins have been associated with the ability of E. coli, and other Gram-negative bacteria, to cause disease. Recently, we described the existence within uropathogenic E. coli (UPEC) strains o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
99
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(107 citation statements)
references
References 43 publications
(86 reference statements)
0
99
1
3
Order By: Relevance
“…These data indicate that pic gene detected in the three pathogens (2,22,37) is active and that, based on their secretion features, the protein is autosecreted to the extracellular medium and thereby to the intestinal lumen during bacterial infection.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…These data indicate that pic gene detected in the three pathogens (2,22,37) is active and that, based on their secretion features, the protein is autosecreted to the extracellular medium and thereby to the intestinal lumen during bacterial infection.…”
Section: Discussionmentioning
confidence: 78%
“…Other authors have shown that Pic does not produce cytotoxic effects on HEp-2 cells during 5 h of incubation and is unable to degrade ovine spectrin or pepsin but that is able to degrade human coagulation factor V (12). In contrast, PicU (from UPEC) degraded human spectrin as well as pepsin, coagulation factor V, and bovine submaxillary gland mucus (37). Due to these contradictory results and to the fact that pic is found in three important pathogens (EAEC, S. flexneri, and UPEC), our group sought to identify intestinal substrates for Pic.…”
mentioning
confidence: 96%
“…Phenotypes identified for Pic suggest that it is involved in the early stages of pathogenesis and most probably promotes intestinal colonization (196). Recently, a homologue, PicU (96% identity at the amino acid level), with similar functions has been characterized in uropathogenic E. coli (381). Subsequent investigations by Heimer et al (194) revealed that picU was expressed during experimental infection in the mouse model of urinary tract infection.…”
Section: Serine Protease Autotransporters Of the Enterobacteriaceaementioning
confidence: 99%
“…which, like the immunoglobulin A1 (IgA1) proteases and Hap autotransporters of Neisseria and Haemophilus spp., possess a consensus serine protease motif (19). Since the description of the first SPATE (30), a number of investigators have described SPATE proteins in the different pathotypes of E. coli and in Shigella (2,9,12,16,27). SPATE proteins possess several common features: (i) all possess an unusual extended signal sequence, (ii) the serine protease active site is reminiscent of a chymotrypsin clan protease, (iii) unlike the IgA1 proteases, none of the SPATE family has been shown to cleave IgA1, (iv) the serine protease motif of SPATE proteins does not have a role in cleavage of the passenger domain from the ␤-domain, (v) the point of cleavage of passenger domains from the ␤-domains is identical, (vi) each SPATE member is among the predominant secreted proteins of their respective pathogens, and (vii) SPATEs are associated with pathogenic strains (18).…”
mentioning
confidence: 99%